Proton-driven sucrose symport and antiport are provided by the vacuolar transporters SUC4 and TMT1/2 - Schulz, Alexander; Poschet, Gernot; Büttner, Michael (The plant journal, 2011)
The vacuolar membrane is involved in solute uptake into and release from the vacuole, which is the largest plant organelle. In addition to inorganic ions and metabolites, large quantities of protons and sugars are shuttled across this membrane. Current models suggest that the proton gradient across the membrane drives the accumulation and/or release of sugars. Recent studies have associated AtSUC4 with the vacuolar membrane. Some members of the SUC family are plasma membrane proton/sucrose symporters. In addition, the sugar transporters TMT1 and TMT2, which are localized to the vacuolar membrane, have been suggested to function in proton-driven glucose antiport. Here we used the patch-clamp technique to monitor carrier-mediated sucrose transport by AtSUC4 and AtTMTs in intact Arabidopsis thaliana mesophyll vacuoles. In the whole-vacuole configuration with wild-type material, cytosolic sucrose-induced proton currents were associated with a proton/sucrose antiport mechanism. To identify the related transporter on one hand, and to enable the recording of symporter-mediated currents on the other hand, we electrophysiologically characterized vacuolar proteins recognized by Arabidopsis mutants of partially impaired sugar compartmentation. To our surprise, the intrinsic sucrose/proton antiporter activity was greatly reduced when vacuoles were isolated from plants lacking the monosaccharide transporter AtTMT1/TMT2. Transient expression of AtSUC4 in this mutant background resulted in proton/sucrose symport activity. From these studies, we conclude that, in the natural environment within the Arabidopsis cell, AtSUC4 most likely catalyses proton-coupled sucrose export from the vacuole. However, TMT1/2 probably represents a proton-coupled antiporter capable of high-capacity loading of glucose and sucrose into the vacuole.